The effectiveness of benson's relaxation technique to reduce pain intensity: A systematic review - Husnul Mubarok; Ahmad Ikhlasul Amal; Dyah Wiji Puspita Sari; Dwi Retno Sulistyaningsih (Holistik Jurnal Kesehatan, 2026)
Background: Pain is a major clinical issue in both acute and chronic patients, affecting quality of life and causing psychological distress. Pharmacological therapy, particularly opioids, remains widely used but has limitations in the form of side effects and the risk of dependence. This has spurred the development of nonpharmacological interventions, one of which is Benson’s Relaxation Technique (BRT), which triggers a relaxation response and has the potential to reduce pain perception. Purpose: To evaluate the effectiveness of BRT in reducing pain intensity across various clinical populations. Method: A literature search was conducted using three databases—PubMed, ScienceDirect, and Web of Science—for articles published between 2015 and 2025. Included studies comprised randomized controlled trials and quasi-experimental designs assessing the effectiveness of BRT. Risk of bias was analyzed using the Joanna Briggs Institute critical appraisal tools. Results: Of the 705 articles identified, nine studies met the inclusion criteria, involving a total of 644 participants from India and Iran. Most studies demonstrated a significant reduction in pain intensity following BRT intervention, either as a standalone treatment or in combination with other therapies such as aromatherapy and psychoeducational interventions. Implementation protocols varied between 10–40 minutes per session with a frequency of 1–3 times per day, yet the results remained consistent. A risk of bias assessment indicated acceptable methodological quality. Conclusion: BRT has been proven to be an effective, safe, adaptable, and easy-to-practice complementary method for reducing pain. With its flexible and non-invasive nature, this technique has the potential to reduce reliance on pharmacological therapies. Large-scale, cross-cultural clinical trials are needed to confirm its long-term effectiveness.   Keywords: Benson's Relaxation Technique; Non-Pharmacological Therapy; Pain Intensity; Relaxation.   Pendahuluan: Nyeri merupakan masalah klinis utama pada pasien akut maupun kronis yang berdampak pada kualitas hidup dan beban psikologis. Terapi farmakologis, khususnya opioid, masih banyak digunakan tetapi memiliki keterbatasan berupa efek samping dan risiko ketergantungan. Hal ini mendorong berkembangnya intervensi nonfarmakologis, salah satunya Benson’s Relaxation Technique (BRT) yang memicu respon relaksasi dan berpotensi menurunkan persepsi nyeri. Tujuan: Untuk mengevaluasi efektivitas BRT dalam menurunkan intensitas nyeri pada berbagai populasi klinis. Metode: Pencarian literatur dilakukan melalui tiga database yaitu PubMed, ScienceDirect, dan Web of Science untuk publikasi artikel tahun 2015–2025. Studi yang disertakan meliputi uji acak terkontrol dan desain kuasi-eksperimental yang menilai efektifitas BRT. Risiko bias dianalisis dengan menggunakan Joanna Briggs Institute critical appraisal tools. Hasil: Dari 705 artikel yang teridentifikasi, sembilan studi memenuhi kriteria inklusi dengan total 644 responden dari Negara India dan Iran. Sebagian besar penelitian menunjukkan penurunan intensitas nyeri yang signifikan setelah intervensi BRT, baik secara mandiri maupun dikombinasikan dengan terapi lain seperti aromaterapi dan intervensi psikoedukatif. Protokol pelaksanaan bervariasi antara 10–40 menit per sesi dengan frekuensi 1–3 kali per hari, namun hasil tetap konsisten. Penilaian risiko bias menunjukkan kualitas metodologi yang dapat diterima. Simpulan: BRT terbukti sebagai metode komplementer yang efektif, aman, adaptif, serta mudah dipraktikkan untuk mengurangi nyeri. Dengan sifatnya yang fleksibel dan non-invasif, teknik ini berpotensi mengurangi ketergantungan pada terapi farmakologis. Uji klinis berskala besar dan lintas budaya diperlukan untuk memastikan efektivitas jangka panjangnya.   Kata Kunci: Benson's Relaxation Technique; Pain Instensity; Relaksasi; Terapi Non-Farmakologis.